Inequality and public policy in Asia - Asadullah, M Niaz (Penerbit Universiti Kebangsaan Malaysia, 2022)
Inequality is on the rise in many parts of Asia despite decades of economic growth and falling poverty. The concern over widening income and wealth gaps has further increased following the COVID-19 pandemic, which has also revived the discussion on the role of public policy in ensuring more equal market outcomes and social opportunities. This guest editorial introduces the special issue proposed by the Global Labor Organization (GLO) on inequality in Asia which includes ten papers by academics and policy researchers. The authors present contrasting research perspectives and evidence using a variety of datasets, methodologies and country experiences to better understand the evolution of inequality and its underlying causes. More specifically, they assess the role of educational expansion, population aging, migration, structural change, trade liberalization, public expenditure and social protection programs in inequality reduction. A number of policy actions are considered to tackle rising inequality such as addressing shortfalls in social expenditure, making social protection systems more inclusive and rethinking the governance of international labor migration. The recommendations also emphasize building on the lessons learnt from the pandemic.